Gentle Rebel: Letters of Eugene V. Debs - Dick, W. M. (Labour / Le Travail, 1997)
The article reviews the book, "Gentle Rebel: Letters of Eugene V. Debs," edited by J. Robert Constantine.
Keywords: BOOKS -- Reviews; CONSTANTINE, J. Robert; GENTLE Rebel: Letters of Eugene V. Debs (Book); Nonfiction; STRIKES & lockouts